Analysis of the clinical efficacy of leuprolide acetate in the treatment of obese patients with endometriosis and its role on the expression of MIF gene - Zhang, Jing; Dong, Liang; Zhang, Shuzhen; Wang, Lei (Cellular and Molecular Biology, 2022)
Endometriosis is an invasive but benign disease of women that develops in endometrial glands outside the endometrium and uterine muscle. It affects about 15-20% of women of childbearing age. One effective way to treat endometriosis is to use GnRH agonists, which inhibit estrogen production. However, one of the possible side effects of this treatment is obesity and BMI increasing, which is a concern for some patients. This study investigated the role of leuprolide acetate in treating overweight patients (BMI≥30) and their comparison with non-overweight patients (BMI<30) for six months. Also, the effect of this medicine was evaluated on the expression of the MIF gene, which is an effective gene in obesity. For this purpose, a clinical trial was performed on 75 women with endometriosis aged 18 to 35 years. These patients were divided into two groups. The first group consisted of 38 patients with BMI<30. The second group consisted of 37 patients with BMI≥30. Both groups were treated with leuprolide acetate at a dose of 3.75 mg/month (intramuscularly) for six months. In addition to clinical evaluations, the expression of the MIF gene was assessed by the real-time PCR technique. The results showed that treatment with leuprolide acetate during six months in both groups reduced dysmenorrhea, dyspareunia, and chronic pelvic pain (P<0.05). Although this decrease was greater in the BMI <30 group, the difference was not significant. Also, after collecting the side effects of the medication, it was found that hypoestrogenism, such as cramps and spotting, was more in the first group; Endogenous complications such as oily skin, acne, and hirsutism were also more common in the second group. The results of MIF gene expression showed that the expression level before and after the start of the experiment in the second group (BMI≥ 30) is higher than the first group (BMI <30). The results also showed that the two groups increased the expression of the MIF gene after treatment with leuprolide acetate. This increase was statistically significant in the second group (P = 0.042). Generally, it was found that this medication causes more weight gain in obese people and increases the risk of obesity-related diseases among these patients. Therefore, it is recommended that this treatment be used with caution in obese patients with endometriosis.